Antimicrobial susceptibility of bacteria isolated from various clinical specimens in a private hospital in Kuching - A retrospective study - Siow-Phing, Tay; Jin-Shyan, Wong; Aldryn Banyie, Baja; Nur Amira, Azizul Hisham; Siti Nur Adibah, Zawawi; Vidyaa Shree, Shanmugha Sundar; Henry, Rantai Gudum (College of Pathologists, Academy of Medicine Malaysia, 2021)
Introduction: Antimicrobial resistance is an emerging global health problem that impacts quality of patient care. Bacterial spectrum and antimicrobial susceptibility vary among countries and regions. Selection of empirical antibiotic therapy should be guided by local microbial profile and antimicrobial susceptibility pattern. This retrospective study was conducted at Borneo Medical Centre in Sarawak to determine the profile of bacteria isolated from various clinical specimens with their antibiotic susceptibility patterns. Materials & Methods: All the 2728 clinical specimens sent for bacterial culture and sensitivity from January to December 2018 were included in this study. Clinical and laboratory data were extracted from the hospital digital database. Results & Discussion: There were 31.3% of samples yielded positive cultures. Most frequently isolated gram-positive bacteria were Staphylococcus spp. (19.8%), Streptococcus spp. (5.9%) and Enterococcus spp. (3.9%). Most frequently isolated gram-negative bacteria were Escherichia coli (20.4%), Pseudomonas spp. (12.8%) and Klebsiella spp. (11.3%). E. coli was the commonest pathogen isolated from urine and blood. Klebsiella spp. and Staphylococcus aureus were most isolated from sputum and wound, respectively. Ceftriaxone was sensitive against Klebsiella spp. (94.9%), E. coli (86.0%) and Pseudomonas spp. (50.0%). Ceftazidime was sensitive against Pseudomonas spp. (94.3%), Klebsiella spp. (91.3%) and E. coli (86.4%). S. aureus and Streptococcus spp. showed 100% sensitivity to vancomycin. Resistance rate of gram-negative bacteria to third generation cephalosporins was low (15.2%). Rates of MRSA (4.1%) and ESBL producing bacteria (1.9%) were also low. Conclusions: Antibiotic resistance rate of the commonly isolated bacteria in this study was low. The commonly used first-line antibiotics are still effective.